Music sheet maker and generator (mobile applications) - Leong, Yuan Ling (2020)
A mobile application is developed in this project, which is Music Sheet Maker and Generator. It is named as CnG music where C stands for composing and G stands for generating. The problem statements of this project are difficulty in getting a music sheet and composing music. Hence, this mobile application is able to generate music sheet for music players, especially for those newbies. In this project, it allows conversion from music to music sheet. This means that a music producer is able to generate music sheet from music. They can also compose their own music in term of the rhythm of the music, the pitch, music pattern and tempo of the music. In this project, waterfall development methodology is used in developing this application. This is because there are some additional functions could be added when it is applicable. The scope of the project is to generate the music sheet from the music and music composer. All the functions will mainly focus on one instrument which is piano. The music sheet is piano sheet and the music composition will also compose by using the keyboard piano provided. By using this mobile application, music players can learn a new song easily and help them in composing a song as well.